2000
DOI: 10.1071/mf99053
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected relationships between coral reef health and socio-economic pressures in the Philippines: reefbase/RAMP applied

Abstract: The paper analyses variables hypothesized to affect the health of coral reefs. These variables include fishing pressure as measured by fisher density and land-based human activities as indicated by population, relative wealth, waste disposal and aspects of land use. Findings indicating that the healthiest coral reef areas are characterized by higher fisher densities as well as greater increases in population density were, at first, surprising. In retrospect, the results fit perfectly with human ecological theo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 9 publications
1
5
0
Order By: Relevance
“…Pollnac et al (2010) found a variable relationship between the density of human populations close to reserves and the biomass of commercially exploited fish species inside reserves relative to control areas. Both positive and negative effects of dense human populations have also been found in other regional studies (Pollnac et al 2000;McClanahan et al 2006) suggesting that positive reserve effects due to fishing restraints might be obscured or overridden by negative effects caused by influences outside reserve boundaries. Besides fishing pressure, the majority of human influences on marine ecosystems are driven by inputs from the land (Halpern et al 2008;Beger et al 2010).…”
Section: Introductionsupporting
confidence: 55%
See 1 more Smart Citation
“…Pollnac et al (2010) found a variable relationship between the density of human populations close to reserves and the biomass of commercially exploited fish species inside reserves relative to control areas. Both positive and negative effects of dense human populations have also been found in other regional studies (Pollnac et al 2000;McClanahan et al 2006) suggesting that positive reserve effects due to fishing restraints might be obscured or overridden by negative effects caused by influences outside reserve boundaries. Besides fishing pressure, the majority of human influences on marine ecosystems are driven by inputs from the land (Halpern et al 2008;Beger et al 2010).…”
Section: Introductionsupporting
confidence: 55%
“…Both positive and negative effects of dense human populations have also been found in other regional studies (Pollnac et al . ; McClanahan et al . ) suggesting that positive reserve effects due to fishing restraints might be obscured or overridden by negative effects caused by influences outside reserve boundaries.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study in the Philippines found a positive relationship between coral health, as measured by a mortality index, and fisher density and the rate of increase in population density (16). These findings were explained by human mobility: fishers simply migrating from damaged and over-fished reefs to more intact reefs with better fishing.…”
Section: Resultsmentioning
confidence: 75%
“…In some cases, displaced fishing may be offset by the spillover effects of a reserve, particularly for settlement-limited fisheries (17). However, in an open-access fishery with high human migration, as in parts of the WIO, fishers might migrate to effective reserves that provide better fishing grounds (16,18). Because methods of counting fish differed among regions, we could not test for separate effects on fish biomass outside and inside reserves.…”
Section: Resultsmentioning
confidence: 99%
“…My results (Lynch 2006) show that fishers' selections of locations are strongly associated with particular habitats, but their locations are more heterogeneously distributed than the mapped habitat types used as biodiversity-planning surrogates (Ward et al 1999). This is not surprising because targeted species are not uniformly distributed (Heagney et al 2007), even in apparently homogeneous habitats (Winberg et al 2007), and fishers are known to target habitat that has been determined as high quality by measures independent of the fisheries (Pollnac et al 2000). Interestingly, like fishing effort, these patterns of biological heterogeneity are often patchy at similarly small spatial scales and, at least for reef fish assemblages, temporally stable.…”
Section: Discussionmentioning
confidence: 95%